SMC sheet formula for new energy battery and preparation process thereof

CN122978655APending Publication Date: 2026-10-27SHENZHEN WORLD WIDE NEW ENERGY TECH CO LYD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611129862.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]然而现有的阻燃型SMC复合材料存在缺陷,SMC复合材料阻燃体系仅靠金属水合物吸热阻燃机理,高温下脱水反应迅速且不可持续,在火场中长时间暴露后阻燃效果急剧衰减,无法满足新能源电池包在电芯热失控时持续耐高温冲击的安全要求,同时SMC复合材料未对树脂基体进行增韧与耐电解液腐蚀改性,电池包在长期使用中若发生电解液泄漏,树脂基体易被溶胀侵蚀导致绝缘失效,且缺乏对高压击穿场景的针对性防护设计,难以保障新能源电池包在复杂工况下的长期可靠运行

Benefits of technology

本发明提供了一种新能源电池用SMC片材配方及其制备工艺:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978655A_ABST
    Figure CN122978655A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of new energy battery preparation, and particularly relates to a SMC sheet formula for new energy batteries, which is made of the following components in parts by mass: 45-70 parts of unsaturated resin, 20-35 parts of flame-retardant aid, 30-40 parts of polytetrafluoroethylene, 1-2 parts of quartz powder, 2-5 parts of colorant, and 15-25 parts of alkali-free chopped glass fiber; the unsaturated resin is made of epoxy resin and epoxy vinyl resin in a mass ratio of 1:2; the metal hydrate is dehydrated and endothermic at high temperature to delay the thermal runaway temperature rise rate; the phosphorus-based flame-retardant component generates a phosphoric acid glassy protective layer on the surface of the material at a sustained high temperature to inhibit the release of flammable gas, ensure that the flame-retardant effect of the sheet does not attenuate in long-time fire exposure, smoothly pass the UL94 V0 level flame-retardant test, and improve the sustained high-temperature impact resistance when the battery cell is in thermal runaway.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new energy battery manufacturing technology, specifically to a formulation and manufacturing process for SMC sheets used in new energy batteries. Background Technology

[0002] The battery pack casing is a key structural component for ensuring the safety of battery cells. Traditional metal casings suffer from problems such as heavy weight, insufficient insulation performance, and limited thermal runaway protection. SMC (sheet molding compound) composite materials are gradually becoming an important material choice for battery pack casings due to their advantages such as lightweight, high strength, and high design freedom.

[0003] The SMC material and production process for new energy vehicle battery packs disclosed in application number CN202211168759.1 is also an increasingly mature technology. Its components include unsaturated resin, flame retardant additives, polytetrafluoroethylene, graphite powder, colorant, and glass fiber. By weight: unsaturated resin 45-70 parts, flame retardant additives 20-35 parts, polytetrafluoroethylene 30-40 parts, quartz powder 1-2 parts, colorant 2-5 parts, and glass fiber 15-25 parts. A resin paste is prepared, and the prepared resin paste is evenly scraped onto a high-density fiberboard (HDF) substrate. On a high-density polyethylene film, 15-25 parts of glass fiber are chopped and evenly dispersed on the film coated with resin paste. The film is then conveyed to the pressure rollers, where the resin paste and alkali-free glass fiber are fully impregnated to form a sheet. Finally, the sheet is wound into a roll or folded into a cloth shape by a winding machine. The resulting sheet is then thickened at 40-45℃ for 6-12 hours to obtain SMC sheet molding compound. This compound is placed in a mold at a molding temperature of 145-155℃ and held under pressure for a period of time. After mold closing, demolding, and trimming, the final product is obtained.

[0004] However, existing flame-retardant SMC composite materials have defects. The flame-retardant system of SMC composite materials relies solely on the endothermic flame-retardant mechanism of metal hydrates. The dehydration reaction at high temperatures is rapid and unsustainable. After prolonged exposure in a fire, the flame-retardant effect decreases sharply, which cannot meet the safety requirements of new energy battery packs to withstand continuous high-temperature impacts during cell thermal runaway. At the same time, SMC composite materials do not toughen or modify the resin matrix to resist electrolyte corrosion. If electrolyte leakage occurs during long-term use of the battery pack, the resin matrix is ​​easily swollen and eroded, leading to insulation failure. Furthermore, there is a lack of targeted protection design for high-voltage breakdown scenarios, making it difficult to ensure the long-term reliable operation of new energy battery packs under complex working conditions.

[0005] Therefore, it is necessary to provide a formulation and preparation process for SMC sheets used in new energy batteries to solve the above problems. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a formulation and preparation process for SMC sheets used in new energy batteries, solving the problems mentioned in the background art.

[0007] To achieve the above objectives, the present invention provides the following technical solution: a formulation for SMC sheet for new energy batteries, which is made of the following components in parts by weight: 45-70 parts of unsaturated resin, 20-35 parts of flame retardant additive, 30-40 parts of polytetrafluoroethylene, 1-2 parts of quartz powder, 2-5 parts of colorant and 15-25 parts of alkali-free chopped glass fiber. The unsaturated resin is composed of epoxy resin and epoxy vinyl resin in a mass ratio of 1:2; The flame retardant additive compound comprises a metal inorganic flame retardant component and a phosphorus-based flame retardant component. The metal inorganic flame retardant component is at least two of antimony trioxide, magnesium hydroxide, and aluminum hydroxide. The phosphorus-based flame retardant component is a compound of two or more of diammonium hydrogen phosphate, disodium hydrogen phosphate, lithium phosphate, sodium phosphate, magnesium phosphate, and antimony phosphate. The SMC sheet is thickened at a constant temperature of 40-45℃ for 6-12 hours, and then molded at 145-155℃ to obtain the new energy battery pack shell, which has UL94V0 flame retardancy and a volume resistivity of 10. 13 cm insulation and resistance to thermal runaway and high-temperature impact of the battery cell.

[0008] Preferably, the optimal mass ratio of each component is: 60 parts unsaturated resin, 25 parts flame retardant additive, 35 parts polytetrafluoroethylene, 1.5 parts quartz powder, 3 parts colorant, and 20 parts alkali-free chopped glass fiber.

[0009] Preferably, the alkali-free chopped glass fiber has a length of 12-24 mm, a fiber areal density controlled at 280-450 g / m², and the fiber is randomly and uniformly dispersed inside the sheet without any local fiber agglomeration blank areas.

[0010] Preferably, the polytetrafluoroethylene is an ultrafine powder with a particle size of 5-15 μm, uniformly dispersed within the resin matrix, which improves the sheet's resistance to electrolyte corrosion and its low-friction thermal conductivity barrier properties.

[0011] Preferably, the quartz powder is high-insulation fused silica powder with a silica content of 99.5%, which fills the resin matrix to improve the breakdown voltage and dimensional thermal stability of the material.

[0012] Preferably, the preparation process of the SMC sheet formulation for new energy batteries includes the following continuous control steps: S1. Integrated mixing of resin paste: Add unsaturated resin, flame retardant, ultrafine polytetrafluoroethylene powder, fused silica powder and colorant in sequence according to the formula, disperse and stir at high speed for 30 to 60 minutes, stirring speed 800 to 1200 r / min, and keep the temperature at 25 to 30℃ to obtain a homogeneous resin paste without particle agglomeration. S2. Double-sided film coating, impregnation and fiber laying pretreatment: The resin paste is evenly coated on the surface of the lower high-density polyethylene carrier film, and short chopped alkali-free glass fibers are evenly spread. Another layer of high-density polyethylene film is covered on the upper layer. The two rollers press and impregnate the fibers simultaneously. The pressure of the rollers is 0.8-1.5MPa and the conveying speed is 3-8m / min, so that the resin paste completely impregnates the fibers to form a sandwich composite sheet. S3. Constant temperature closed-loop thickening and curing: After the sandwich composite sheet is rolled up / folded, it is sent into a closed constant temperature thickening chamber. The temperature inside the chamber is constant at 40-45℃ and the relative humidity is 40%-60%. Thickening is continued for 6-12 hours to complete the thickening reaction of the resin system and obtain a moldable SMC sheet molding compound. S4. Battery pack housing molding: The thickened SMC sheet is cut and placed into the mold. The mold is heated to a constant temperature of 145-155℃, and the mold is closed and pressed at 8-15MPa for 2-5 minutes. The mold is closed, cured, cooled and demolded, and the edges are trimmed in sequence to obtain the SMC protective housing of the new energy battery pack.

[0013] Preferably, the viscosity of the resin paste is monitored online in real time during the mixing process in step S1, with the viscosity control range being 8000-15000 mPas. If the viscosity exceeds the standard, the stirring time and ambient temperature are automatically adjusted.

[0014] Preferably, in step S2, the pressing and impregnation process is equipped with online surface density detection, which collects data on resin coating amount and fiber laying amount in real time, and adjusts the fiber cutting speed of the scraper gap in conjunction with the process to ensure that the overall surface density deviation of the sheet is within 3%.

[0015] Preferably, the thickening chamber in step S3 is equipped with multi-point temperature sensors. If the temperature difference between any two points in the chamber is 1°C, an automatic audible and visual alarm will be triggered if the temperature exceeds the time limit and the production batch data will be recorded.

[0016] Preferably, step S4 compression molding uses a segmented temperature-controlled mold with a mold cavity temperature difference of 2°C. The holding pressure is increased in stages, with a low pre-pressure of 2MPa maintained for 30s before being increased to the rated holding pressure to eliminate internal bubbles and delamination defects in the product.

[0017] Compared with the prior art, the beneficial effects of the present invention are: This invention provides a formulation and preparation process for SMC sheets used in new energy batteries: 1. By constructing a multi-dimensional flame-retardant structure that combines a metallic inorganic flame-retardant component (at least two of antimony trioxide, magnesium hydroxide, and aluminum hydroxide) with a phosphorus-based flame-retardant component (phosphate compound), a dual flame-retardant mechanism is facilitated by heat absorption and cooling and char formation of the condensed phase. The metal hydrate dehydrates and absorbs heat at high temperatures, slowing down the rate of thermal runaway. The phosphorus-based flame-retardant component generates a phosphate-based glassy protective layer at continuous high temperatures, covering the material surface and inhibiting the release of flammable gases. This ensures that the flame-retardant effect of the sheet does not decrease during long-term exposure to fire, successfully passing the UL94 V0 flame-retardant test and improving the continuous high-temperature impact resistance of the battery cell during thermal runaway.

[0018] 2. By using epoxy resin and epoxy vinyl resin in a 1:2 ratio as an unsaturated resin matrix, the cross-linking density and solvent resistance of the resin matrix are improved by utilizing the unsaturated double bonds and epoxy groups in the epoxy vinyl resin molecular chain. The ultrafine polytetrafluoroethylene powder (particle size 5-15 μm) uniformly dispersed in the matrix has low surface energy and chemical inertness, which can effectively block the swelling and penetration channels of the electrolyte into the resin matrix. The filling of high-insulation fused silica powder (silica content 99.5%) effectively improves the volume resistivity (10 cm⁻¹) and breakdown voltage of the material, thereby preventing the new energy battery pack from operating reliably for a long time in the event of electrolyte leakage. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the process flow of the present invention; Figure 2 This is a comparative table of SMC sheet formulation examples for new energy batteries according to the present invention; Figure 3 This is a comparative table of four embodiments of the SMC sheet for the new energy battery pack of the present invention. Detailed Implementation

[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] Example 1 A formulation for SMC sheet for new energy batteries is made from the following components by weight: 45 parts unsaturated resin, 20 parts flame retardant additive, 30 parts polytetrafluoroethylene, 1 part quartz powder, 2 parts colorant and 15 parts alkali-free chopped glass fiber. Unsaturated resin is a compound of epoxy resin and epoxy vinyl resin in a mass ratio of 1:2. The flame retardant additive compound contains a metal inorganic flame retardant component and a phosphorus-based flame retardant component. The metal inorganic flame retardant component is a compound of antimony trioxide and aluminum hydroxide, and the phosphorus-based flame retardant component is a compound of diammonium hydrogen phosphate and magnesium phosphate. The alkali-free chopped glass fiber is 12mm in length, and the fiber areal density is controlled at 280g / ㎡. The fiber is randomly and uniformly dispersed inside the sheet, with no local fiber agglomeration or blank areas. Polytetrafluoroethylene is an ultrafine powder with a particle size of 5 μm, which is uniformly dispersed in the resin matrix to improve the sheet's resistance to electrolyte corrosion, low friction, and thermal conductivity barrier properties. The quartz powder is a highly insulating fused silica powder with a silica content of 99.5%. It is used to fill the resin matrix to improve the breakdown voltage and dimensional thermal stability of the material.

[0022] The preparation process of the SMC sheet formulation for new energy batteries in this embodiment includes the following continuous control steps: S1. Integrated mixing of resin paste: Unsaturated resin, flame retardant additive, ultrafine polytetrafluoroethylene powder, fused silica powder and colorant are added in sequence according to the formula. The mixture is dispersed and stirred at high speed for 30 minutes at a stirring speed of 800 r / min and constant temperature of 25℃ to obtain a homogeneous resin paste without particle agglomeration. The viscosity of the resin paste is monitored online in real time during the mixing process, and the viscosity control range is 8000 mPas. S2. Double-sided film coating, impregnation, and fiber laying pretreatment: The resin paste is evenly coated onto the surface of the lower high-density polyethylene (HDPE) support film, and short-cut alkali-free glass fibers are evenly spread. Another layer of HDPE film is then placed on top, and the film is simultaneously pressed and impregnated by two rollers. The roller pressure is 0.8 MPa, and the conveying speed is 3 m / min, so that the resin paste completely impregnates the fibers to form a sandwich composite sheet. The pressing and impregnation process is equipped with online surface density detection to collect real-time data on the amount of resin coating and fiber laying. The gap between the scrapers and the fiber chopped output speed are adjusted to ensure that the overall surface density deviation of the sheet is within 3%. S3. Constant Temperature Closed-Loop Thickening and Curing: After the sandwich composite sheet is rolled up, it is sent into a sealed constant temperature thickening chamber. The temperature inside the chamber is constant at 40℃ and the relative humidity is 40%. Thickening is carried out continuously for 6 hours to complete the thickening reaction of the resin system and obtain a moldable SMC sheet molding compound. The thickening chamber is equipped with multiple temperature sensors. The temperature difference between any two points inside the chamber is 1℃. If the timeout or temperature exceeds the limit, an automatic audible and visual alarm will be triggered and the production batch data will be recorded. S4. Battery Pack Shell Molding: The thickened SMC sheet is cut and placed into the mold. The mold is heated to a constant temperature of 145℃ and the pressure is maintained at 8MPa for 2 minutes. A segmented temperature-controlled mold is used with a temperature difference of 2℃ in the mold cavity. The pressure is increased in stages. The low pressure pre-pressurization of 2MPa is maintained for 30 seconds and then increased to the rated pressure. The mold is closed, cured, cooled, demolded, and the edges are trimmed in sequence to obtain the SMC protective shell of the new energy battery pack.

[0023] In this embodiment, the SMC sheet prepared is thickened at a constant temperature of 40°C for 6 hours, and then molded at 145°C to obtain a new energy battery pack shell, which has UL94V0 flame retardancy, 10cm volume resistivity insulation and resistance to high temperature impact from thermal runaway of the battery cell.

[0024] Example 2 A formulation for SMC sheets used in new energy batteries is made from the following components by weight: 50 parts unsaturated resin, 23 parts flame retardant additive, 33 parts polytetrafluoroethylene, 1.2 parts quartz powder, 3 parts colorant, and 18 parts alkali-free chopped glass fiber. Unsaturated resin is a compound of epoxy resin and epoxy vinyl resin in a mass ratio of 1:2. The flame retardant additive compound contains a metal inorganic flame retardant component and a phosphorus-based flame retardant component. The metal inorganic flame retardant component is a compound of magnesium hydroxide and aluminum hydroxide, and the phosphorus-based flame retardant component is a compound of disodium hydrogen phosphate and lithium phosphate. The alkali-free chopped glass fiber is 16mm in length, and the fiber areal density is controlled at 340g / ㎡. The fiber is randomly and uniformly dispersed inside the sheet, with no local fiber agglomeration or blank areas. Polytetrafluoroethylene is an ultrafine powder with a particle size of 9 μm, which is uniformly dispersed in the resin matrix to improve the sheet's resistance to electrolyte corrosion, low friction and thermal conductivity barrier properties. The quartz powder is a highly insulating fused silica powder with a silica content of 99.5%. It is used to fill the resin matrix to improve the breakdown voltage and dimensional thermal stability of the material.

[0025] The preparation process of the SMC sheet formulation for new energy batteries in this embodiment includes the following continuous control steps: S1. Integrated mixing of resin paste: Unsaturated resin, flame retardant, ultrafine polytetrafluoroethylene powder, fused silica powder and colorant are added in sequence according to the formula. The mixture is dispersed and stirred at high speed for 40 minutes at a stirring speed of 1000 r / min and kept at a constant temperature of 27℃ to obtain a homogeneous resin paste without particle agglomeration. The viscosity of the resin paste is monitored online in real time during the mixing process, and the viscosity control range is 11000 mPas. S2. Double-sided film coating, impregnation, and fiber laying pretreatment: The resin paste is evenly coated onto the surface of the lower high-density polyethylene (HDPE) support film, and short-cut alkali-free glass fibers are evenly spread. Another layer of HDPE film is then placed on top, and the film is pressed and impregnated simultaneously by two rollers. The pressure rollers have a linear pressure of 1.1 MPa and a conveying speed of 5 m / min, ensuring that the resin paste completely impregnates the fibers to form a sandwich composite sheet. The pressing and impregnation process is equipped with online surface density detection to collect data on the amount of resin coating and fiber laying in real time. The gap between the scrapers and the speed of the chopped fiber output are adjusted accordingly to ensure that the overall surface density deviation of the sheet is within 3%. S3. Constant Temperature Closed-Loop Thickening and Curing: The sandwich composite sheet is folded into a cloth shape and fed into a sealed constant temperature thickening chamber. The temperature inside the chamber is constant at 42℃ and the relative humidity is 50%. Thickening is carried out continuously for 9 hours to complete the thickening reaction of the resin system and obtain a moldable SMC sheet molding compound. The thickening chamber is equipped with multiple temperature sensors. The temperature difference between any two points inside the chamber is 1℃. If the temperature exceeds the time limit, an automatic audible and visual alarm will be triggered and the production batch data will be recorded. S4. Battery Pack Shell Molding: The thickened SMC sheet is cut and placed into the mold. The mold is heated to a constant temperature of 150℃, and the mold is closed and pressed at 12MPa for 3.5 minutes. A segmented temperature-controlled mold is used, with a temperature difference of 2℃ in the mold cavity. The pressure is increased in stages. The low pressure pre-pressurization of 2MPa is maintained for 30 seconds and then increased to the rated pressure. The mold closing, curing, cooling and demolding and edge trimming are completed in sequence to obtain the SMC protective shell of the new energy battery pack.

[0026] In this embodiment, the SMC sheet prepared is thickened at a constant temperature of 42°C for 9 hours, and then molded at 150°C to obtain a new energy battery pack shell, which has UL94V0 flame retardancy, 10cm volume resistivity insulation and resistance to high temperature impact from cell thermal runaway.

[0027] Example 3 A formulation for SMC sheet for new energy batteries is made from the following components by weight: 60 parts unsaturated resin, 25 parts flame retardant additive, 35 parts polytetrafluoroethylene, 1.5 parts quartz powder, 3 parts colorant, and 20 parts alkali-free chopped glass fiber. Unsaturated resin is a compound of epoxy resin and epoxy vinyl resin in a mass ratio of 1:2. The flame retardant additive compound contains a metal inorganic flame retardant component and a phosphorus-based flame retardant component. The metal inorganic flame retardant component is a compound of antimony trioxide, magnesium hydroxide, and aluminum hydroxide, while the phosphorus-based flame retardant component is a compound of diammonium hydrogen phosphate, sodium phosphate, and antimony phosphate. The alkali-free chopped glass fiber is 20mm in length, and the fiber areal density is controlled at 380g / ㎡. The fiber is randomly and uniformly dispersed inside the sheet, with no local fiber agglomeration or blank areas. Polytetrafluoroethylene is an ultrafine powder with a particle size of 10 μm, which is uniformly dispersed in the resin matrix to improve the sheet's resistance to electrolyte corrosion, low friction and thermal conductivity barrier properties. The quartz powder is a highly insulating fused silica powder with a silica content of 99.5%. It is used to fill the resin matrix to improve the breakdown voltage and dimensional thermal stability of the material.

[0028] The preparation process of the SMC sheet formulation for new energy batteries in this embodiment includes the following continuous control steps: S1. Integrated mixing of resin paste: Unsaturated resin, flame retardant, ultrafine polytetrafluoroethylene powder, fused silica powder, and colorant are added sequentially according to the formula. The mixture is dispersed and stirred at high speed for 45 minutes at a stirring speed of 1000 r / min, and kept at a constant temperature of 28℃ to obtain a homogeneous resin paste free of particle agglomeration. The viscosity of the resin paste is monitored online in real time during the mixing process, with a viscosity control range of 12000 mPas. S2. Double-sided film coating, impregnation, and fiber laying pretreatment: The resin paste is evenly coated onto the surface of the lower high-density polyethylene (HDPE) support film, and short-cut alkali-free glass fibers are evenly spread. Another layer of HDPE film is then placed on top, and the film is simultaneously pressed and impregnated by two rollers. The pressure rollers have a linear pressure of 1.2 MPa and a conveying speed of 6 m / min, ensuring that the resin paste completely impregnates the fibers to form a sandwich composite sheet. The pressing and impregnation process is equipped with online surface density detection to collect real-time data on resin coating amount and fiber laying amount. The gap between the scrapers and the fiber chopped output speed are adjusted accordingly to ensure that the overall surface density deviation of the sheet is within 3%. S3. Constant temperature closed-loop thickening and curing: The sandwich composite sheet is rolled up and sent into a sealed constant temperature thickening chamber. The temperature inside the chamber is constant at 43°C and the relative humidity is 50%. Thickening is carried out continuously for 10 hours to complete the thickening reaction of the resin system and obtain a moldable SMC sheet molding compound. The thickening chamber is equipped with multiple temperature sensors. The temperature difference between any two points inside the chamber is 1°C. If the temperature exceeds the time limit, an automatic audible and visual alarm will be triggered and the production batch data will be recorded. S4. Battery Pack Shell Molding: The thickened SMC sheet is cut and placed into the mold. The mold is heated to a constant temperature of 150℃, and the mold is closed and pressed at 12MPa for 3 minutes. A segmented temperature-controlled mold is used, with a temperature difference of 2℃ between the mold cavity and the pressure is increased in stages. The low pressure pre-pressurization of 2MPa is maintained for 30 seconds and then increased to the rated pressure. The mold is closed, cured, cooled, demolded, and the edges are trimmed in sequence to obtain the SMC protective shell for the new energy battery pack.

[0029] This embodiment represents the optimal formulation. The SMC sheet is thickened at a constant temperature of 43°C for 10 hours and then molded at 150°C to obtain the casing of the new energy battery pack. It has UL94V0 flame retardancy, 10cm volume resistivity insulation and resistance to high temperature impact from thermal runaway of the battery cell. It has the best overall flame retardancy, insulation, mechanical properties, temperature resistance and corrosion resistance.

[0030] Example 4 A formulation for SMC sheet for new energy batteries is made from the following components by weight: 70 parts unsaturated resin, 35 parts flame retardant additive, 40 parts polytetrafluoroethylene, 2 parts quartz powder, 5 parts colorant, and 25 parts alkali-free chopped glass fiber. Unsaturated resin is a compound of epoxy resin and epoxy vinyl resin in a mass ratio of 1:2. The flame retardant additive compound contains a metal inorganic flame retardant component and a phosphorus-based flame retardant component. The metal inorganic flame retardant component is a compound of two types: antimony trioxide and magnesium hydroxide, and the phosphorus-based flame retardant component is a compound of three types: lithium phosphate, magnesium phosphate, and antimony phosphate. The alkali-free chopped glass fiber is 24mm in length, and the fiber areal density is controlled at 450g / ㎡. The fiber is randomly and uniformly dispersed inside the sheet, with no local fiber agglomeration or blank areas. Polytetrafluoroethylene is an ultrafine powder with a particle size of 15 μm, which is uniformly dispersed in the resin matrix to improve the sheet's resistance to electrolyte corrosion, low friction and thermal conductivity barrier properties. The quartz powder is a highly insulating fused silica powder with a silica content of 99.5%. It is used to fill the resin matrix to improve the breakdown voltage and dimensional thermal stability of the material.

[0031] The preparation process of the SMC sheet formulation for new energy batteries in this embodiment includes the following continuous control steps: S1. Integrated mixing of resin paste: Unsaturated resin, flame retardant additive, ultrafine polytetrafluoroethylene powder, fused silica powder and colorant are added in sequence according to the formula. The mixture is dispersed and stirred at high speed for 60 minutes at a stirring speed of 1200 r / min and kept at a constant temperature of 30℃ to obtain a homogeneous resin paste without particle agglomeration. The viscosity of the resin paste is monitored online in real time during the mixing process, and the viscosity control range is 15000 mPas. S2. Double-sided film coating, impregnation, and fiber laying pretreatment: The resin paste is evenly coated onto the surface of the lower high-density polyethylene (HDPE) support film, and short-cut alkali-free glass fibers are evenly spread. Another layer of HDPE film is then placed on top, and the film is simultaneously pressed and impregnated by two rollers. The pressure rollers have a linear pressure of 1.5 MPa and a conveying speed of 8 m / min, ensuring that the resin paste completely impregnates the fibers to form a sandwich composite sheet. The pressing and impregnation process is equipped with online surface density detection to collect real-time data on resin coating amount and fiber laying amount. The gap between the scrapers and the fiber chopped output speed are adjusted accordingly to ensure that the overall surface density deviation of the sheet is within 3%. S3. Constant Temperature Closed-Loop Thickening and Curing: The sandwich composite sheet is folded into a cloth shape and fed into a sealed constant temperature thickening chamber. The temperature inside the chamber is constant at 45℃ and the relative humidity is 60%. Thickening is carried out continuously for 12 hours to complete the thickening reaction of the resin system and obtain a moldable SMC sheet molding compound. The thickening chamber is equipped with multiple temperature sensors. The temperature difference between any two points inside the chamber is 1℃. If the temperature exceeds the time limit, an automatic audible and visual alarm will be triggered and the production batch data will be recorded. S4. Battery Pack Shell Molding: The thickened SMC sheet is cut and placed into the mold. The mold is heated to a constant temperature of 155℃, and the mold is closed and held at a pressure of 15MPa for 5 minutes. A segmented temperature-controlled mold is used, with a temperature difference of 2℃ between the mold cavity and the holding pressure is increased in stages. The low pressure pre-pressurization of 2MPa is maintained for 30 seconds and then increased to the rated holding pressure. The mold closing, curing, cooling and demolding and edge trimming are completed in sequence to obtain the SMC protective shell of the new energy battery pack.

[0032] In this embodiment, the SMC sheet prepared is thickened at a constant temperature of 45°C for 12 hours and then molded at 155°C to obtain a new energy battery pack shell, which has UL94V0 flame retardancy, 10cm volume resistivity insulation and resistance to high temperature impact from thermal runaway of the battery cell.

[0033] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

[0034] It should be noted that, in this document, the terms include, encompass, or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, including an element by a statement does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element. Furthermore, it should be noted that the scope of the methods and apparatuses in the embodiments of this application is not limited to performing functions in the order shown or discussed, but may also include performing functions substantially simultaneously or in the reverse order, depending on the functions involved. For example, the described methods may be performed in a different order than described, and various steps may be added, omitted, or combined. Additionally, features described with reference to certain examples may be combined in other examples.

[0035] The embodiments of this application have been described above with reference to the accompanying drawings. However, this application is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of this application without departing from the spirit and scope of the claims, and all of these forms are within the protection scope of this application.

Claims

1. A formulation for SMC sheets used in new energy batteries, characterized in that, It is made from the following components by weight: 45-70 parts unsaturated resin, 20-35 parts flame retardant additive, 30-40 parts polytetrafluoroethylene, 1-2 parts quartz powder, 2-5 parts colorant, and 15-25 parts alkali-free chopped glass fiber. The unsaturated resin is composed of epoxy resin and epoxy vinyl resin in a mass ratio of 1:2; The flame retardant additive compound comprises a metal inorganic flame retardant component and a phosphorus-based flame retardant component. The metal inorganic flame retardant component is at least two of antimony trioxide, magnesium hydroxide, and aluminum hydroxide. The phosphorus-based flame retardant component is a compound of two or more of diammonium hydrogen phosphate, disodium hydrogen phosphate, lithium phosphate, sodium phosphate, magnesium phosphate, and antimony phosphate. The SMC sheet is thickened at a constant temperature of 40-45℃ for 6-12 hours, and then molded at 145-155℃ to obtain the new energy battery pack shell, which has UL94V0 flame retardancy and a volume resistivity of 10. 13 cm insulation and resistance to thermal runaway and high-temperature impact of the battery cell.

2. The SMC sheet formulation for new energy batteries according to claim 1, characterized in that: The optimal mass ratio of each component is as follows: 60 parts unsaturated resin, 25 parts flame retardant additive, 35 parts polytetrafluoroethylene, 1.5 parts quartz powder, 3 parts colorant, and 20 parts alkali-free chopped glass fiber.

3. The SMC sheet formulation for new energy batteries according to claim 1, characterized in that: The alkali-free chopped glass fibers have a length of 12-24 mm and a fiber areal density controlled at 280-450 g / m². The fibers are randomly and uniformly dispersed inside the sheet, with no local fiber agglomeration blank areas.

4. The SMC sheet formulation for new energy batteries according to claim 1, characterized in that: The polytetrafluoroethylene is an ultrafine powder with a particle size of 5-15 μm, which is uniformly dispersed in the resin matrix to improve the sheet's resistance to electrolyte corrosion and low frictional heat conduction barrier properties.

5. The SMC sheet formulation for new energy batteries according to claim 1, characterized in that: The quartz powder is a high-insulation fused silica powder with a silica content of 99.5%, which is filled into the resin matrix to improve the breakdown voltage and dimensional thermal stability of the material.

6. A preparation process for the SMC sheet formulation for new energy batteries according to any one of claims 1 to 5, characterized in that, It includes the following continuous control steps: S1. Integrated mixing of resin paste: Add unsaturated resin, flame retardant, ultrafine polytetrafluoroethylene powder, fused silica powder and colorant in sequence according to the formula, disperse and stir at high speed for 30 to 60 minutes, stirring speed 800 to 1200 r / min, and keep the temperature at 25 to 30℃ to obtain a homogeneous resin paste without particle agglomeration. S2. Double-sided film coating, impregnation and fiber laying pretreatment: The resin paste is evenly coated on the surface of the lower high-density polyethylene carrier film, and short chopped alkali-free glass fibers are evenly spread. Another layer of high-density polyethylene film is covered on the upper layer. The two rollers press and impregnate the fibers simultaneously. The pressure of the rollers is 0.8-1.5MPa and the conveying speed is 3-8m / min, so that the resin paste completely impregnates the fibers to form a sandwich composite sheet. S3. Constant temperature closed-loop thickening and curing: After the sandwich composite sheet is rolled up / folded, it is sent into a closed constant temperature thickening chamber. The temperature inside the chamber is constant at 40-45℃ and the relative humidity is 40%-60%. Thickening is continued for 6-12 hours to complete the thickening reaction of the resin system and obtain a moldable SMC sheet molding compound. S4. Battery pack housing molding: The thickened SMC sheet is cut and placed into the mold. The mold is heated to a constant temperature of 145-155℃, and the mold is closed and pressed at 8-15MPa for 2-5 minutes. The mold is closed, cured, cooled and demolded, and the edges are trimmed in sequence to obtain the SMC protective housing of the new energy battery pack.

7. The preparation process of an SMC sheet formulation for new energy batteries according to claim 6, characterized in that: In step S1, the viscosity of the resin paste is monitored online in real time during the mixing process. The viscosity control range is 8000-15000 mPas. If the viscosity exceeds the standard, the stirring time and ambient temperature are automatically adjusted.

8. The preparation process of an SMC sheet formulation for new energy batteries according to claim 6, characterized in that: In step S2, the pressing and impregnation process is equipped with online surface density detection to collect real-time data on resin coating amount and fiber laying amount, and to adjust the fiber cutting speed of the scraper gap in conjunction with the process to ensure that the overall surface density deviation of the sheet is within 3%.

9. The preparation process of an SMC sheet formulation for new energy batteries according to claim 6, characterized in that: Step S3: The thickening chamber is equipped with multiple temperature sensors. If the temperature difference between any two points in the chamber is 1°C, an automatic audible and visual alarm will be triggered if the temperature exceeds the time limit and the production batch data will be recorded.

10. The preparation process of an SMC sheet formulation for new energy batteries according to claim 6, characterized in that: Step S4 compression molding uses a segmented temperature-controlled mold with a mold cavity temperature difference of 2℃. The holding pressure is increased in stages, with a low pre-pressure of 2MPa held for 30s before being increased to the rated holding pressure to eliminate internal bubbles and delamination defects in the product.

Citation Information

Patent Citations

  • SMC material for new energy automobile battery pack and production process

    CN115627053A